1995
DOI: 10.1083/jcb.129.6.1707
|View full text |Cite
|
Sign up to set email alerts
|

Components of the nuclear signaling cascade that regulate collagenase gene expression in response to integrin-derived signals.

Abstract: Abstract. We have shown previously that the expression of collagenase is upregulated in rabbit synovial fibroblasts cultured on a substrate of antibody to the o~5 chain of the et5131 integrin fibronectin receptor or on the 120-kD cellbinding chymotryptic fragment of plasma fibronectin, but remains at basal levels in cells plated on intact plasma fibronectin. We now have identified some of the components of a signaling pathway that couples the fibronectin receptor to the induction of collagenase transcription. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
59
0
2

Year Published

1996
1996
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(62 citation statements)
references
References 76 publications
1
59
0
2
Order By: Relevance
“…When G0-syncronized cells are plated on FN-coated dishes, early growth response genes, such as c-fos, c-myc, and c-jun, are rapidly induced (Dike and Farmer, 1988;Eierman et al, 1989;Tremble et al, 1995;Varner et al, 1995;Dike and Ingber, 1996). We show that STAT5A activated by integrinmediated adhesion binds to the SIE oligonucleotide sequence, a known STAT target region in the c-fos promoter (Zhong et al, 1994).…”
Section: Expression Of a Dominant Negative Stat5a Protein Drasticallymentioning
confidence: 99%
See 1 more Smart Citation
“…When G0-syncronized cells are plated on FN-coated dishes, early growth response genes, such as c-fos, c-myc, and c-jun, are rapidly induced (Dike and Farmer, 1988;Eierman et al, 1989;Tremble et al, 1995;Varner et al, 1995;Dike and Ingber, 1996). We show that STAT5A activated by integrinmediated adhesion binds to the SIE oligonucleotide sequence, a known STAT target region in the c-fos promoter (Zhong et al, 1994).…”
Section: Expression Of a Dominant Negative Stat5a Protein Drasticallymentioning
confidence: 99%
“…Integrin-induced signaling has been reported to affect gene expression (Dike and Farmer, 1988;Haskill et al, 1991;Chen et al, 1992;Rana et al, 1994;Schmidhauser et al, 1994;Fan et al, 1995;Tremble et al, 1995;Dike and Ingber, 1996). Among the early growth response genes encoding for transcriptional activators, adhesion-dependent induction of cfos gene transcription has been described in monocytes (Haskill et al, 1991), in endothelial cells (Dike and Ingber, 1996;Wary et al, 1996), and in fibroblasts (Tremble et al, 1995;Wary et al, 1996) and proposed as a mediator of cell cycle progression controlled by cell adhesion.The signaling pathways leading to integrin-dependent early growth response gene transcription are not completely defined. A role of activated Erk1/Erk2 MAP kinases in coupling integrins to gene expression has been recently proposed (Chen et al, 1992;Morino et al, 1995;Zhu and Assoian, 1995;Wary et al, 1996).…”
mentioning
confidence: 99%
“…AP-1 activity and target gene expression are a ected by interaction of the cell with extracellular matrix proteins and alterations of the actin cytoskeleton, which can activate other transcription factors (Chang et al, 1998;Clarke et al, 1998;Lorenzi et al, 1999;Treisman et al, 1998;Tremble et al, 1995;Troussard et al, 1999;Westermarck and Kahari, 1999;Wisdom, 1999).…”
Section: Northern Analysismentioning
confidence: 99%
“…Recent studies showed that integrins may also play an important role in the control of gene expression. Exposure of rabbit synovial fibroblasts to fibronectin fragments or anti-FN receptor antibody induces the expression of metalloproteinase, stromelysin, and a 92-kDa gelatinase (15)(16)(17)(18). Overexpression of ␣ 5 ␣ 1 in human colon carcinoma HT29 cells induces the transcription of growth arrest-specific gene 1 (GAS-1) and blocks the transcription of immediate early genes c-FOS, c-JUN, and JUN-B (19).…”
mentioning
confidence: 99%